Laser induced cavitations with a holographic grating. - Lim, Kang Yuan. (2009)
In this work the dynamics of laser induced cavitation bubbles is studied with methods of high-speed photography. In the first part of this project we report on the importnac of the geometry. The bubbles are created in liquid gaps of different heights, in this way we were able to reveal the importance of constraining the flow. In the unconstrained case we find a good agreement with the 3 dimensional Rayleigh-Plesset equation describing the collapse of a bubble in an infinite liquid. In constrained geometries, the bubble dynamics is modified and a lifetime of the bubble is observed, in particular, the collapse phase is retarded. On the second part, different shaped bubbles are created with a spatial light modulator. Three different ways are demonstrated to obtain bubbles of non-spherical shape, e.g. 4-sided (rectangular) bubbles, donut-shaped bubbles, triangular bubbles, love-shaped bubbles, oval-shaped bubble, and jet forming V-shaped bubbles.